EVALUASI EFEKTIFITAS PENGUJIAN SISTEM INFORMASI KUBIKASI BARANG DENGAN METODE BLACK BOX DAN WHITE BOX TESTING DI PT XYZ - Nita Winda Sari; Santo Wijaya; Nandan Muliawan (Politeknik META Industri Cikarang, 2025)
PT XYZ, as a partner of PT ABC Technologies, has an important role in the manufacturing and distribution process of electronic products, including the management of logistics warehouses. The previously used goods cubication information system was based on Excel, but faced various obstacles such as data inaccuracy and delays in accessing information. This study uses a quantitative approach with Black Box and White Box testing methods to measure the effectiveness of the developed application. The Equivalence Partitioning technique is also used to simplify the number of test cases without reducing the scope of testing. The test results show that the system functions according to specifications, with no logical errors found. The use of a combination of testing methods has proven effective in identifying system deficiencies. In addition, the survey results show a high level of user satisfaction with the performance and ease of the system. The goods cubication information system developed is able to improve the accuracy and efficiency of warehouse operations. This study contributes to software testing and recommends regular monitoring and implementation of user feedback for future system improvements